Application of scenario analysis in Market Risk Management of Commercial Banks: International Practice and Case Studies - Chen Jun (Research Retrieval and Academic Letters, 2025)
In the context of global economic integration, increased volatility in financial markets, and increased geopolitical uncertainty, the market risks faced by commercial banks are becoming more and more complex and severe.Traditional risk management tools, such as the Value at Risk (VaR) model, although they play an important role in quantifying daily risks, have significant limitations in capturing extreme market events and systemic risks.The 2008 global financial crisis and the subsequent series of events such as the “London Whale” have exposed the risk of over-reliance on a single quantitative model, prompting the global banking industry and regulators to re-examine and strengthen the risk management framework.In this context, Scenario Analysis (Scenario Analysis), as a forward-looking risk management tool that can assess the potential losses of banks under specific and usually extremely unfavorable conditions, has become increasingly important.Scenario analysis can not only help banks identify and quantify “tail risks” that cannot be covered by traditional models, but also provide management with deep insights into strategic resilience, capital adequacy, and risk mitigation strategies, thereby transforming risk management from passive compliance requirements to active strategic advantages.